Plasticity in ascending long propriospinal and descending supraspinal pathways in chronic cervical spinal cord injured rats - Côté, Marie-Pascale (Frontiers Media S.A., 2012)
The high clinical relevance of models of incomplete cervical spinal cord injury (SCI) creates a need to address the spontaneous neuroplasticity that underlies changes in functional activity that occur over time after SCI. There is accumulating evidence supporting long projecting propriospinal neurons as suitable targets for therapeutic intervention after SCI, but focus has remained primarily oriented toward study of descending pathways. Long ascending axons from propriospinal neurons at lower thoracic and lumbar levels that form inter-enlargement pathways are involved in forelimb-hindlimb coordination during locomotion and are capable of modulating cervical motor output. We used non-invasive magnetic stimulation to assess how a unilateral cervical (C5) spinal contusion might affect transmission in intact, long ascending propriospinal pathways, and influence spinal cord plasticity. Our results show that transmission is facilitated in this pathway on the ipsilesional side as early as 1 week post-SCI. We also probed for descending magnetic motor evoked potentials (MMEPs) and found them absent or greatly reduced on the ipsilesional side as expected. The frequency-dependent depression (FDD) of the H-reflex recorded from the forelimb triceps brachii was bilaterally decreased although H(max)/M(max) was increased only on the ipsilesional side. Behaviorally, stepping recovered, but there were deficits in forelimb–hindlimb coordination as detected by BBB and CatWalk measures. Importantly, epicenter sparing correlated to the amplitude of the MMEPs and locomotor recovery but it was not significantly associated with the inter-enlargement or segmental H-reflex. In summary, our results indicate that complex plasticity occurs after a C5 hemicontusion injury, leading to differential changes in ascending vs. descending pathways, ipsi- vs. contralesional sides even though the lesion was unilateral as well as cervical vs. lumbar local spinal networks.